EFEKTIVITAS KEPEMIMPINAN KETUA KELOMPOK TANI DALAM DIFUSI INOVASI PENGELOLAAN TANAMAN TERPADU PADI DI KABUPATEN LAMPUNG SELATAN - Furi Tiara Anggunanda; Tubagus Hasanuddin; Indah Nurmayasari (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2016)
This study aims to determine: the leadership effectiveness of farmer groups leader, factors related to the leadership effectiveness of farmer groups leader, diffusion of innovation rate of integrated paddy crop cultivation, and related between the leadership effectiveness and the speed of diffusion of innovation integrated paddy crop cultivation. This research was conducted in the Palas Jaya Village and Pulau Tengah Village Palas District of South Lampung regency. The research samples were drawn by purposive sampling in whiich the total sample were 64 farmers, 16 leadership of farmer groups and 48 members of farmer groups. The study was conducted from January to February 2016 by survey method.  The relationship between variables was tested by Spearman Rank correlation test.  The results showed that the leadership effectiveness of farmer groups leader at Palas Jaya Village and Pulau Tengah Village was effective,  factors related to the leadership effectiveness of farmer groups leader were motivation of farmer groups leader, enthusiastic of farmer groups leader, and the responsibilities of farmer groups leader, the rate of diffusion of integrated paddy crop cultivation in the Palas Jaya Village and Pulau Tengah Village included in the category of fast enough,  there wasn’t relation between the leadership effectiveness of farmer groups leader and the speed of diffusion of integrated paddy crop cultivation in the Palas Jaya Village and Pulau Tengah Village.Key words: diffusion of innovation, integrated paddy crop cultivation, leadership